Հայերէնի եւ պոլինեզիական լեզուների հնչյունական որոշ յատկանիշների զուգադրական համեմատություն - Լեյլա Ստեփանյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В результате сопоставительного сравнения армянского и полинезийских языков, в частности, рапануйского (остров Пасхи), обнаружены общие фонетические особенности. Некоторые из них выявлены между рапануйским и протоармянским, а звуковое соответствие глухой звонкий, характерная для родственных языков, обнаруживается между рапанануйским и древнеармянским (грабар). Some common phonetic characteristics have been revealed as a result of a comparative study of the Armenian and some Polynesian languages (the Rapanui language spoken on Easter Island, in particular). Some of them are revealed between Rapanui and Ancient Armenian languages, and the deaf-sonorous phonetic correspondence characteristic of related languages is found between Rapanui and the Classical Armenian language.
Keywords: Language and Literature